Comunicação pública nas redes sociais: o caso do governo do estado do Rio Grande do Sul a luz dos valores democráticos - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Social media has brought a new tool for social discussions in the social arena, the emergence of social networks (be it Twitter, Facebook, Orkut, MSN and others) provided that the relationship between public power and society narrows what once seemed inconceivable with these technologies became a reality. The environment encouraged citizens to have opportunities to express themselves, expressing their ideas, critiques (both positive and negative), praise, dissatisfaction with the public manager. In this sense, it is Democracia Digital, stating that whatever initiative is aimed at fostering civil participation in democratic decisions or favoring the environment for them. For these reasons, governments started to adopt these social networks as a way of communicating with the population and the way these media were used was regulated by SECOM (2013) through a manual that indicated what behavior should be followed by governments, public bodies of direct and indirect manager. Within the communication aspect it is divided into two: Governmental (dealing with the manager's political agenda) and Public (about government actions, accountability, management data and etc.), being that the Public Communication in the last one had a significant growth, facilitated by the use of social networks, mainly of Facebook, that at the moment is the network more owns users. Contextualizing this type of communication with the traditional one used by the other media, Barros and Miola (2015) bring democratic values regarding public communication in the virtual social media, which would be: Transparency, Accountability, Participation and Provision of Services. From this perspective, this study established as general objective, to know the form of communication and participation used by the Government of the State of Rio Grande do Sul on its Facebook page, having as specific objectives: a) to analyze the fanpage of the Government of Rio Grande do Sul; b) classify the publications according to the model of democratic values brought by Barros (2014); c) identify whether the level of participation of followers is occurring satisfactorily. The Government fanpage has 335,206 tanned and has a daily average of 4.95 publications; It was found that most of the publications are classified in the Other category, representing 44.96%. However, if the democratic values were analyzed Transparência is the one that obtained the most publications, accounting for 26.54%, followed by Provision of Services (12.94 %), Participation (12.06%) and Accountability (3.51%). Since follower interaction during the analysis period was low if we compare with the total fanpage followers. It can be verified in this study that the Government of Rio Grande do Sul uses its fanpage as a way of propagating different information, but following the democratic value of Transparency, insofar as it works on information about its actions and government programs, maintaining a relation of proximity to its users / citizens.
Keywords: Comunicação Pública; Redes Sociais; Democracia digital; Valores democráticos; Communication; Social networks; Digital democracy; Democratic values; CNPQ::CIENCIAS SOCIAIS APLICADAS